Topical Film-Forming Chlorhexidine Gluconate Sprays for Antiseptic Application - Benchawan Chamsai; Sirima Soodvilai; Praneet Opanasopit; Wipada Samprasit (MDPI AG, 2022)
Topical film-forming sprays of chlorhexidine gluconate (CHG-FFS) were developed for antiseptic application. Various polymers and solvents were studied for their potential as film-forming polymers and solvent systems, respectively. To produce CHG-FFS, the optimal polymer and solvent were selected, and their physicochemical properties were evaluated. The in vivo evaluation of CHG-FFS was investigated for the satisfaction of the dosage forms, time required for the film formation, film appearance, and adhesion on the skin. Antibacterial activity was also studied in vitro and in vivo. The optimized formulation was assessed for the in vitro cell line evaluations of the cytotoxicity and wound healing. The results demonstrate that Eudragit® S100, Eudragit® L100, and polyvinyl alcohol (PVA) have the ability to be used as film-forming polymers in an ethanolic solution. A clear and flexible film was obtained from transparent homogenous solutions of CHG-FFS after actuation. They generated the fast thin film formation on the skin with the satisfaction of the dosage forms. Furthermore, the formulations inhibited the growth of Staphylococcus aureus in vitro and provided antiseptic activity in vivo. However, PVA was found to be an optimal film-forming polymer for promoting CHG adhesion on the skin. The CHG-FFS obtained from the PVA also provided a CHG film, which was non-toxic to human skin cells and did not interfere with the wound healing process. Therefore, the developed CHG-FFS could be a promising candidate for topical antiseptic application.